Peran Influencer Dalam Menentukan Pengaruh Sosial Media Youtube Terhadap Intensi Pembelian HP Samsung Seri A di Tangerang Selatan - Farelieyano, Alrakashya; Ali, Sampor (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to identify and analyze moderate Islamic marketing strategies that are effective in attracting and maintaining the loyalty of young millennials in the digital era. This study uses a quantitative method based on positivism to analyze the influence of YouTube influencers on the purchase intention of Samsung A Series HP in South Tangerang. With multiple linear regression and classical assumption tests using SPSS, this study measures the relationship between the role of influencers and social media on purchasing decisions. The results are expected to provide insight for companies in designing more effective digital marketing strategies through the YouTube platform. The findings of this study are expected to provide insight for companies in designing more effective digital marketing strategies that are in accordance with the trends of young consumer behavior. This study concludes that the role of influencers and YouTube social media has a positive and significant influence on the purchase intention of Samsung A Series HP in South Tangerang. Partially, influencers who are effective in explaining products can increase consumer purchasing interest, as well as social media that provides good information. In addition, simultaneously, the combination of the role of influencers and social media contributes significantly to encouraging consumer purchasing decisions for the product.